DIFFERENTIATED INSTRUCTION IN ENGLISH LEARNING, TEACHING AND ASSESSMENT IN NON-LANGUAGE UNIVERSITIES - Larysa Kupchyk; Alona Litvinchuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2020)
This paper is aimed at resolving the problem of inadequate level of foreign language proficiency of students in non-language institutions of higher education and discussing effective approaches and methods to improve foreign language instruction at tertiary schools. An analysis of the problem by means of mixed research methods revealed the need to create positive and motivating foreign language learning environment on the basis of preliminary diagnosis through the evidence-based instructional strategies and assessment tools that make a difference in student achievements. The authors substantiate the expediency of applying differentiated instruction as a means of fostering foreign language learning by students of non-language majors, which was proved by the results of the conducted experiment. 116 Bachelor students of the National University of Water and Environmental Engineering in their first year of study took part in the experiment, which was held in academic years 2016-2017 and 2017-2018. The experiment started with the placement test, the results of which allowed grouping first-year students according to their prior knowledge of English into different groups from A1 to B2 CEFR levels. The differentiated instruction was performed in homogenous groups by means of the level-relevant content and materials, teaching methods and assessment tools. The research findings allowed the authors to contribute to improving the course design, implementing differentiated lessons, choosing appropriate teaching methods and gathering feedback. The conducted experiment also helped draw conclusions on the improvement of foreign language learning under newly created conditions, adding to high rate of productivity and flexibility of learning paths. An analysis of the experimental data showed that differentiated instruction can significantly increase students' motivation to foreign language acquisition and learning outcomes.